Dietary Factors and the Risk of Gastric Cancer in Hanzhong Area of China - Cheng Wang; Sanjun He; Weimin Jin; Luanluan Zheng; Rui Jin; Sichuan Feng; Ying Zhou; Hanqiu Tang; Haixia Liu; Yi Si (Tehran University of Medical Sciences, 2022)
Background: Dietary factors play an important role in gastric cancer risk. They have not been investigated extensively in Hanzhong area, China. Methods: We conducted a population-based case-control study of gastric cancer in Hanzhong area, China in 2018-2020. A total of 121 patients with historically confirmed gastric adenocarcinomas were interviewed. Controls were an age-stratified random sample of residents of Hanzhong area. The dietary questionnaire was a 70-item semiquantitative food frequency adapted for the Hanzhong diet. Odds ratios were calculated for quartiles of consumption of food groups and were adjusted for age, gender, calories, chili pepper intake, cigarette smoking, socioeconomic status, added salt, and history of peptic ulcer disease. Results: There was approximately a threefold increased risk of gastric cancer for frequent consumption (highest quartile) of both fresh meat (odds ratio (OR) = 3.0) and processed meat (OR = 3.3). Odds ratios were also significantly elevated for frequent consumption of dairy products (OR = 3.1) and fish (OR = 3.1). The authors observed a decreasing gradient of risk with increasing frequency of vegetable consumption due to a significant inverse trend for the yellow and orange vegetables. Conclusion: High intake of citrus fruits showed a slight inverse association. These findings are consistent with many studies around the world that indicate important roles for salt, processed meats, and vegetable consumption in gastric cancer risk.